Diabetic Eye Disease Related Knowledge, Attitudes and Practices among Physicians in Nepal - Pradhan, Eli; Khatri, Anadi; Tuladhar, Jasmeen; Shrestha, Dina (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Background: Awareness of diabetic retinopathy amongst general physicians is a major factor for the prevention of diabetes-related ocular complications.They are most often the first line of contact of diabetic patients and their knowledge and attitude are the principal indicators of their level of awareness. Methods: This cross-sectional study was conducted in Kathmandu and is based on a structured questionnaire referring to Diabetic retinopathy formulated on Guideline for Conducting a Knowledge, Attitude and Practice Study by information, Education, and Communication expert.The questionnaire comprised of 18 questions and 45 physicians were enrolled. Significant differences and associations were determined by values of P < 0.05. Results: All of the physicians (100%) were aware that diabetes can damage the eye and can cause visual impairment. Most of them agreed that patients with diabetes should be sent for ophthalmic evaluations with majority mandating an immediate evaluation after the diagnosis. The majority (98%) of physicians disagreed that eye examination was required only once the vision was affected. Only 56% of the physicians agreed they routinely perform direct ophthalmoscopy to examine the retina (p 0.551). Among them, nearly half (44%) reported not knowing the importance of dilating the pupil. (p=0.69). Conclusions: The study shows a good level of diabetic retinopathy awareness and knowledge with positive attitudes toward the importance of diabetes care. At the same time, it has found that practice level despite good knowledge and attitude to be below average among the physicians who are managing diabetic patients.